Clinical pathological features of breast cancer associated with the expression of the Ki-67 cell marker at Edgardo Rebagliati Martis National Hospital, 2013-2017 - Mayanga Sausa, Silvia Lucia (2019)
Introduction. Breast cancer is the third cause of death in peruvian women, a genetically heterogeneous disease, there are no studies on the behavior of the Ki-67 cell proliferation marker in this population. Objective. To analyze the association between the clinical pathological characteristics of breast cancer and the expression of the Ki-67 antigen in Hospital Nacional Edgardo Rebagliati Martins (HNERM), Lima-Perú. Methods. A retrospective study conducted in diagnostic samples of 209 patients with breast cancer. The clinical pathological characteristics were: age, histological type, tumor size, histological grade, lymphovascular invasion, axillary lymph node, clinical stage (TNMp), RE, RP, Her2+, triple positive, triple negative. The Ki-67 cell marker expression was categorized as low (Ki-67<20%) and high (Ki-67>20%). Results. High expression of the Ki-67 cell marker (>20%) was associated with tumors of 2cm, histological grade 2 and 3, greater number of axillary ganglia affected and Her2+ and triple negative inmunophenotypes. Low expression of Ki-67 (<20%) was associated with estrogen and progesterone positive tumors. Conclusion. The Ki-67 cell marker with high expression (>20%) shows a significant association with characteristics of poor prognosis well known in breast cancer.